Study and investigate perceptions of Jordanian college students on the golden ratio proportions. (October 2022) - Shamaileh, Anas Atef
Abstract: We concentrate on the importance of the golden ratio in the implications of interior design in this paper. The current study aimed to evaluate college students' perspectives toward employing interior designs based on golden ratio proportions. We adopted a quantitative research methodology to identify Jordanian university students' perceptions toward using interior designs based on the golden ratio. Perceived pleasure and comfort are two quantitative indicators utilized in research and development. The outcomes indicated that the participants' reactions were significant because they judged the golden ratio-based forms to be more appealing and comfortable than the normal ones. We employed statistical techniques to analyze the data, and based on the results, we evaluated the influence of golden ratio proportions on the perceptions of Jordanian college students. Based on the findings, the researcher suggests that the golden ratio be given more attention in interior design and higher education applications.